Feeding Ecology, Length-Weight relationship and Condition Factor of Mugil cephalus (Pisces: Mugilidae; Linnaeus, 1758) From Cross River Estuary, Nigeria - Asuquo, Philomena Edet; Eyo, Victor Oscar; Ikechukwu, Chuks C. (My University, 2015)
This study was conducted to investigate the diet composition, length-weight relationship and condition factor of Mugil cephalus from the Cross River estuary, Nigeria, between May 2009 and July 2009. A total of 210 freshly caught specimens of Mugil cephalus were collected from the catches of the artisanal fisheries from the Cross River Estuary, Nigeria. Results obtained showed an allometric growth pattern for this fish species with a significant linear relationship given by the equation: TW= 0.0586SL2.5631 and Log TW = 2.5631LogSL - 1.2318 (r2 = 0.5136, t = 3.768, n = 210, P< 0.05, d.f 208). Variability was observed in the condition factor between months. Mean condition factor highest in May (1.96 ± 0.04) followed by 1.88 ± 0.04 (June) and 1.75 ± 0.05 (July). Mean condition factor (CF) in relation to size class was highest in 10.0 – 12.9 cm size class (2.8 ± 0.02) and lowest in 13.0 1 Corresponding author: sirvick2003@yahoo.com Philomena Edet Asuquo, Victor Oscar Eyo, Chuks C. Ikechukwu- Feeding Ecology, Length-Weight relationship and Condition Factor of Mugil cephalus (Pisces: Mugilidae; Linnaeus, 1758) From Cross River Estuary, Nigeria – 15.9 cm size class (1.9 ± 0.04). Length frequency distribution of M. cephalus showed that standard length class of 16 – 18.9 cm had the highest frequency of 96 samples, followed by 13.0 – 15.9 cm length class (56), followed by 19.0 – 21.9 length class (39) and 10.0 – 12.9 cm length class (19). A total of 35 different diet components were obtained with numerical abundance of 1709. As a result of the high abundance of Synedra acus (185, 9.65%), copepods (175, 10.24%), Celothrix sp (102, 5.97 %), Mud/sand (102, 5.32%) and Skelotonema costatum (98, 5.97%) in the gut of Mugil cephalus this species was classified as heterotrophy detrivore/invertivore and filter feeder. The occurrence of shrimps (6,031%), fish bones (19,0.99%), copepod legs (37, 1.93%) and fish scales (!6,0.3%) implies that Mugil cephalus is an opportunistic feeder. This study has not only identified Muguil cephalus as a herbivorous feeder but has also provided information for future trophic modeling of the Cross River estuary.
Keywords: Mugil cephalus; Diet composition; Length-weight relationship; Condition factor; Cross River Estuary; Length frequency distribution